2016
DOI: 10.1016/j.jand.2015.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Diets High in Fiber and Vegetable Protein Are Associated with Low Lumbar Bone Mineral Density in Young Athletes with Oligoamenorrhea

Abstract: Background Associations of bone mineral density (BMD) with specific food components, including dietary fiber and isoflavones (that have a negative association with serum estrogen), are unclear and need to be determined, particularly in a population more likely to consume large amounts of these nutrients (such as young athletes). Objective To determine dietary intake of specific food components in oligo-amenorrheic athletes (OA) compared to eumenorrheic athletes (EA) and non-athletes (NA), and associations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
(65 reference statements)
1
11
0
4
Order By: Relevance
“…Final calculations were completed using NDSR version 2014 for all visits. Food diaries have been validated for use in children [36, 37], and have been used effectively in studies involving children and adolescents [1, 38, 39]. Activity levels were assessed using the Youth Physical Activity Survey (YPAS) and categorized as ‘Sedentary’, ‘Low Active’, ‘Active’, and ‘Very Active’ (personal communication from Cincinnati Children’s Hospital Medical Center).…”
Section: Methodsmentioning
confidence: 99%
“…Final calculations were completed using NDSR version 2014 for all visits. Food diaries have been validated for use in children [36, 37], and have been used effectively in studies involving children and adolescents [1, 38, 39]. Activity levels were assessed using the Youth Physical Activity Survey (YPAS) and categorized as ‘Sedentary’, ‘Low Active’, ‘Active’, and ‘Very Active’ (personal communication from Cincinnati Children’s Hospital Medical Center).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Cobb et al 3 and Barrack et al 4 reported a 36% and 39% prevalence of low bone mass among a sample of collegiate and high school runners, respectively. Factors previously associated with low bone mass among female endurance runners include elevated dietary restraint, amenorrhea, a longer duration of participation (5 or more vs <5 seasons) in endurance running,4 higher intake of dietary fibre, phytic acid, vegetable protein and history of a stress fracture 6 7. Lower body mass index (BMI thresholds of 18.5 kg/m 2 and 17.5 kg/m 2 ) has been identified as a risk factor for low BMD 7 8.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of the protein source, such as animal protein (including dairy and nondairy products) or vegetable protein, is still debated. For instance, some positive associations between bone health and vegetable protein have been reported (5,28,29), but inconsistently (8,30). The association between bone health and dairy-product intakes has been investigated in both cross-sectional and longitudinal observational studies and in intervention trials with some positive effects [see Rizzoli (31) for a review].…”
Section: Introductionmentioning
confidence: 99%